Sustainable clothing: challenges, barriers and interventions for encouraging more sustainable consumer behaviour. (16th December 2015) - Harris, Fiona; Roby, Helen; Dibb, Sally
Abstract: Research with consumers has revealed limited awareness of the sustainability impact of clothing (Goworek et al ., 2012). Semi‐structured interviews conducted with a range of experts in sustainable clothing to increase understanding of the challenges for sustainable clothing revealed that a focus on sustainability alone will not drive the necessary changes in consumers' clothing purchase, care and disposal behaviour for three reasons: (i) clothing sustainability is too complex; (ii) consumers are too diverse in their ethical concerns and (iii) clothing is not an altruistic purchase. The findings identify the challenges that need to be addressed and the associated barriers for sustainable clothing. Interventions targeting consumers, suppliers, buyers and retailers are proposed that encourage more sustainable clothing production, purchase, care and disposal behaviour. These interventions range from normalizing the design of sustainable clothing and increasing the ease of purchase, to shifting clothes washing norms and increasing upcycling, recycling and repair.